Exile as a configuration of history: Isla de Puerto Rico by María Zambrano (Ogigia. Revista Electrónica de Estudios Hispánicos, 2025)
The study of Spanish exile following the Civil War (1936-1939) has gained prominence in academic research, particularly regarding female writers who, forced to leave their country, developed their intellectual work abroad. Their testimonies have been the subject of detailed analysis due to their uniqueness and the challenges they faced, such as job uncertainty, economic hardship, and adaptation to new communities. Moreover, their status as political exiles provides a unifying thematic axis for their literature. Among these authors, María Zambrano holds a central place. Her work Isla de Puerto Rico, nostalgia y esperanza de un mundo mejor (1940), published in Havana, belongs to the tradition of poetic essays and presents a conception of democracy that transcends the immediate historical context. Through symbolic language, the author intertwines her philosophical and political thought with a vision of intellectual and emotional community. Zambrano distances herself from the Ortega y Gasset model and formulates an essay in which the political dimension takes on a poetic structure—not merely aesthetic, but creative. Through a mythical construction, she envisions the island as a space for historical renewal, linking democracy with the individual's essential freedom and its manifestation in society.
Keywords: Spanish exile; Zambrano; community; democracy; person